Anisotropic magnetoresistance in facing-target reactively sputtered epitaxial γ′-Fe4N films. (May 2015) - Li, Z.R.; Feng, X.P.; Wang, X.C.; Mi, W.B.
Graphical abstract: Highlights: The negative and twofold symmetric AMR appears in epitaxial γ ′-Fe4 N films. The negative AMR can be attributed to the spin-down conduction electron. With the increased temperature, the absolute value of AMR ( | AMR | ) decreases. | AMR | of the (1 0 0)-oriented films is always larger than the (1 1 0)-oriented films. Abstract: The negative anisotropic magnetoresistance that comes from the spin-down conduction electrons are observed in facing-target sputtered epitaxial γ ′-Fe4 N films with different film thicknesses, substrates and orientations. Anisotropic magnetoresistance of γ ′-Fe4 N films on LaAlO3 (1 0 0) is larger than other substrates. The magnitude of anisotropic magnetoresistance in (1 0 0)-oriented films is always larger than (1 1 0)-oriented films. The anisotropic magnetoresistance is intimately related to the magnetocrystalline anisotropy. Fourier coefficient C 2 θ and C 4 θ of cos 2 θ and cos 4 θ terms strongly depend on the measuring temperature. No significant influence of magnetic field on C 2 θ and C 4 θ appears. The marked change of C 2 θ and appearance of C 4 θ at low temperatures are from crystal field splitting of d orbitals induced by the lattice change due to the tensile stress from substrate and the compressive stress from decreased temperatures. A. Magnetic materials; A. Nitrides; B. Epitaxial growth; D. Electrical properties